Framework para desenvolvimento de algoritmos para análise de sinais com problemas de qualidade de energia - Andrade, Jeferson Gustavo de (2019)
The growing search for the dianosis of Eletric Power Quality events by means of mathematical tools applied in computational methods with the purpose of providing observation and correction of disturbances in the delivery of eletric energy, has been a growing area in the study of signal processing. Whether through simulators or equipment capable of measuring QEE events, there is a wide variety of sources capable of providing this data for analysis. Because they are different sources, there is also a difference in the pattern and format of their data. As a consequence, performing the analysis of these data means performing its decoding so that it acquires a compatible structure to be worked by traditional softwares of Engineering. The objective of this work is the study and development of a a framework developed in the Matlab software that helps researchers in the QEE area in the development of algorithms for analyzing signals from simulators or meters, freeing them from the need to perform the previous steps of data compatibility. The framework is capable of reading files with measurements from QEM meters in COMTRADE format, as well as reading two different types of formats, from the simulators ATP and Simulink, widely used in simulations in the field of Electrical Engineering. After reading the data, pre-processing starts, which identifies abnormalities, performs manipulations on variables and adapts the data to a standard format in an input structure that can be processed by several QEE analysis algorithms. To demonstrate the operation of the framework, this work presents a template with an algorithm based on the Wavelet Transform. After processing by the algorithm, the data is saved in an output structure and used to present the results in graphical and statistical formats, in order to provide the best user experience in observing its results.